Wayang Kardus sebagai Media Pembelajaran Kreatif untuk Melestarikan Budaya Lokal di Kabupaten Kediri: Cardboard Puppets as Creative Learning Medium in Preserving Local Cultures in Kediri, Indonesia - Mochammad Nginwanun Likullil Mahamid (Besari: Journal of Social and Cultural Studies, 2024)
This article describes cardboard puppets as an artistic innovation on local culture that adapts puppet art in a simpler form by using used cardboard as its main material. Through descriptive qualitative research, the article aims to examine the function of cardboard puppets as a creative learning medium as well as a means of preserving local culture in Kediri Regency. The results of the study show that cardboard puppets not only reintroduce puppet art to the younger generation, but also become an educational medium that involves students in creative activities. Making cardboard puppets trains motoric skills, improves imagination, instills local wisdom values through the stories told, and instills awareness of the importance of environmental preservation. The cardboard puppets is a concrete example of how traditional art can adapt to the challenges of modernity through innovation.   Artikel ini membahas wayang kardus sebagai inovasi seni budaya lokal yang mengadaptasi seni wayang dalam bentuk lebih sederhana dengan menggunakan kardus bekas sebagai bahan utamanya. Melalui penelitian kualitatif deskriptif, artikel ini mengkaji fungsi wayang kardus sebagai media pembelajaran kreatif sekaligus sarana pelestarian budaya lokal di Kabupaten Kediri. Hasil penelitian menunjukkan bahwa wayang kardus tidak hanya memperkenalkan kembali seni wayang kepada generasi muda, tetapi juga menjadi media pendidikan yang melibatkan siswa dalam aktivitas kreatif. Pembuatan wayang kardus melatih keterampilan motorik, meningkatkan imajinasi, menanamkan nilai-nilai kearifan lokal melalui cerita yang disampaikan, serta menanamkan kesadaran terhadap pentingnya pelestarian lingkungan. Wayang kardus adalah contoh konkret bagaimana seni tradisional dapat beradaptasi dengan tantangan modernitas melalui inovasi.